Knowledge, attitude, and perceptions of Filipino consumers in Calabarzon and Metro Manila toward edible insects and insect-based products - Latina, Andrea Mikaela E. (University of the Philippines Diliman, 2023)
While there are plenty of edible insects in the Philippines, people are still hesitant to incorporate them into their daily meals, despite their significant potential to serve as a viable source of protein. The objective of the present research is to evaluate Filipino consumers' knowledge, attitude, and perception of edible insects and insect-based products, as well as to analyze the factors that affect their consumption by utilizing both an online survey (n = 109) and two sessions of focus group discussions. Results showed that the participants possess a general understanding of the fundamental concepts related to edible insects and insect-based products. However, they also demonstrated knowledge gaps regarding these products' sustainability and nutritional characteristics. The respondents also expressed negative to neutral attitudes towards edible insects and insect-based products wherein significant differences were observed among the respondents from different age groups, occupational statuses, and regions of residence. The main factors for their willingness to consume edible insects and insect-based products include health benefits, taste, and appearance. Meanwhile, unfamiliarity, safety concerns, and disgust were identified as the primary reasons for their apprehension to consume edible insects. The participants evaluated edible insects and insect-based products as of low quality and safety, giving a rating of at least 2.00 (one = very low, two = low, three = moderate, four = high, and five = very high) for all visual presentations. However, products with visible entire insects had significantly lower perceived quality and safety compared to insect-based products where the insects were hidden or incorporated. The results imply that edible insects and insect-based products can be a potential alternative protein source in the Philippines, provided that the misconceptions surrounding them are dealt with by improving information accessibility, increasing availability, and creating visually appealing products.